2013
DOI: 10.1254/jphs.13052sc
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole Does Not Affect Hippocampal Synaptic Plasticity and Spatial Memory, Which Are Impaired by Diazepam in Rats

Abstract: Abstract.We have previously demonstrated that riluzole has anxiolytic-like effects in rats, without affecting spontaneous alternation performance in the Y-maze test. However, the effects of riluzole on hippocampal synaptic plasticity were still unclear. In this study, we showed that bath application of riluzole did not impair long-term potentiation and long-term depression, whereas a benzodiazepine anxiolytic, diazepam, significantly impaired them. Furthermore, the acquisition of spatial memory in the Morris w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… a Subgroup analysis of RCT by Spangler et al (2020). 13 b Riluzole was increased to 200 mg/day for participants not demonstrating at least a 10‐point improvement on the PCL‐S at 2 weeks. c Fluvoxamine, clomipramine, escitalopram, and fluoxetine were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Subgroup analysis of RCT by Spangler et al (2020). 13 b Riluzole was increased to 200 mg/day for participants not demonstrating at least a 10‐point improvement on the PCL‐S at 2 weeks. c Fluvoxamine, clomipramine, escitalopram, and fluoxetine were used.…”
Section: Resultsmentioning
confidence: 99%
“…Spangler et al 13 Low Low Some Low Low Low Pittenger et al 19 Low Low Some Low Some Some Emamzadehfard et al 20 Low Low Some Low Low Low Grant et al 12 Low Low Some Low Low Some study had a low risk of bias except for "bias due to missing outcome data" (Table 2). However, there were no statistically significant differences in any adverse events between the two groups.…”
Section: Overall Risk Of Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also suggested that sheep may have spent more time eating and consequently less time displaying vigilance behavior due to diazepam increasing appetite and not due to an anxiolytic effect of the drug [59,60]. Further, studies in rats have found that diazepam can impair spatial memory or learning [61,62], which may confound responses during attention bias testing if a sheep no longer associates the previous location of the dog with the threat of a dog and does not localize their attention accordingly. Previous studies administering diazepam to sheep have given inconsistent results, with some [32] but not all studies [30,31] observing behavioral responses that are expected to indicate a calm state, such as decreased vigilance during an arena test, decreased agitation in an isolation box and a reduced startle response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, spatial memory or learning may confound animal responses if a test subject no longer associates the previous location of the dog with the threat of a dog and does not localise their attention accordingly. This potentially confounding factor is important to consider when using pharmacological models that may have an impact on spatial memory or learning, as may be the case for diazepam (Brioni and Arolfo 1992;Sasaki-Hamada et al 2013). It may be worthwhile exploring options to balance stimulus presentation times in the attentionbias test in a way that does not increase the intensity of the threat, such as by using a photograph of a dog instead of or in conjunction with a live dog.…”
Section: Stimulus Duration and Intensitymentioning
confidence: 99%